Parasioid Wasps of Eulophinae (Hymenoptera: Eulophidae) in Nusa TenggaraRA TIMUR, INDONESIA - Rosichon Ubaidillah (Research Center for Biology, 2003)
Eulopliid parasitoid wasps of the Enlophinnc III Nusa Tenggara TIII/llr, i ndonesia, were studied taxonomicallu. A total of15 species 111 nine gellern are recorded. From those species eight are described neui toscience. Keys to gel/era and species are presented.Key words: Hymenoptera, Chalcidoidea, Eulophidae, Eulophinae, new record and new species,key, Indonesia, Tirnor, Flores, Sumba